Applied Stress-Assisted Growth of Single Crystal γ-Fe(2)O(3) Nanowires - Lu, Lan (Nanomaterials (Basel), 2018)
It is difficult to obtain γ-Fe(2)O(3) nanostructures by heating iron substrate in ambient conditions because γ-Fe(2)O(3) is less thermodynamically stable than α-Fe(2)O(3). In this work, we synthesize γ-Fe(2)O(3) nanowires by heating iron particles under an external force. The stacking style of iron and oxygen ions under a strong shearing stress tends to adopt the γ-Fe(2)O(3) structure regardless of the thermodynamic restriction. These γ-Fe(2)O(3) nanowires exhibit a clear ferromagnetic property. Transmission electron microscopy (TEM) and X-ray diffraction (XRD) measurements confirm that γ-phase structure appears only under the applied external force during the heating period. A window of the magnitude of the external force is found to help the nanowire growth on iron particles. The growth mechanism of γ-Fe(2)O(3) nanowires other than α-Fe(2)O(3) under the external force is discussed and an applied stress-assisted growth model is proposed. This work presents an easy approach to produce ferromagnetic iron oxide nanowires on a large scale.